A novel signature to predict the neoadjuvant chemotherapy response of bladder carcinoma: Results from a territory multicenter real-world study - Li, Huihuang; Hu, Jiao; Zu, Xiongbing; Chen, Minfeng; Chen, Jinbo; Zou, Yihua; Deng, Ruoping; Qin, Gang; Li, Wenze; Tang, Jiansheng; Deng, Dingshan; Liu, Jinhui; et al. (Frontiers in Genetics, 2022)
Background: Although neoadjuvant chemotherapy (NAC) has become the standard treatment options for muscle invasive bladder carcinoma (MIBC), its application is still limited because of lacking biomarkers for NAC predicting. Methods: We conducted a territory multi-center real-world study to summarize the NAC practice in China and associated the clinicopathologic variables with NAC response. Then we developed and validated a robust gene-based signature for accurate NAC prediction using weighted correlation network analysis (WGCNA), least absolute shrinkage and selector operation (LASSO) algorithm, multivariable binary logistic regression model and immunohistochemistry (IHC). Results: In total, we collected 69 consecutive MIBC patients treated with NAC from four clinical centers. The application of NAC in real-world was relatively safe, with only two grade Ⅳ, seven grade Ⅲ AEs and no treatment related death reported. Among these patients, 16 patients gave up surgery after NAC, leaving 53 patients for further analysis. We divided them into pathological response and non-response groups and found that there were more patients with higher grade and stage in the non-response group. Patients with a pathological response could benefit from a significant overall survival (OS) improving. In addition, univariate and multivariate logistic analysis indicated that tumor grade and clinical T stage were both independently factors for predicating NAC response. Importantly, we developed and validated a five-genes-based risk score for extremely high predicative accuracy for NAC response. Conclusions: NAC was relatively safe and could significantly improve OS for MIBC patients in real-world practice. Our five-genes-based risk score could guide personalized therapy and promote the application of NAC.